2022
DOI: 10.1002/pat.5614
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and investigation potential effect of lentinan and docetaxel nanofibers for synergistic treatment of breast cancer in vitro

Abstract: Breast cancer has a high prevalence among women which has high recurrences even after common therapies, so using nanofibers that contain natural compounds along with antineoplastic drugs locoregionally can be a novel supportive strategy. In this study, hot water extracted lentinan from Lentinula edodes (TMU340) was purified by ion-exchange chromatography. The effects of electrospun PVA/lentinan/docetaxel nanofibers were determined on HER3 expression in MCF-7 cell line. Lentinan concentration was determined at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“… 62 Research has demonstrated that extract-loaded NFs are effective at causing cytotoxicity to BC cells. 66 These NFs’ controlled release method offers a possible means of lowering systemic toxicity and tumor recurrence after surgery. 39 In a similar vein, using piperine (PIP)-PCL75-Coll25 NFs in a 4T1 BC mouse model resulted in a tumor growth suppression that was effective and demonstrated the NFs’ sustained-release capabilities and strong anticancer effectiveness.…”
Section: Plant Extract–loaded Scaffolds In Bc Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“… 62 Research has demonstrated that extract-loaded NFs are effective at causing cytotoxicity to BC cells. 66 These NFs’ controlled release method offers a possible means of lowering systemic toxicity and tumor recurrence after surgery. 39 In a similar vein, using piperine (PIP)-PCL75-Coll25 NFs in a 4T1 BC mouse model resulted in a tumor growth suppression that was effective and demonstrated the NFs’ sustained-release capabilities and strong anticancer effectiveness.…”
Section: Plant Extract–loaded Scaffolds In Bc Treatmentmentioning
confidence: 99%
“… 62 On the contrary, not much is said about how patients receive these scaffolds inserted or how the body reacts to the procedure. 39 , 66 They emphasize how effective drug encapsulation and regulated release can reduce systemic toxicity and the chance of tumor recurrence. 65 However, a complete understanding of the practical implications of the medicines is hampered by the lack of data demonstrating clinical outcomes or patient reactions following therapy.…”
Section: Plant Extract–loaded Scaffolds In Bc Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Lentinan enhances the production of T lymphocytes and can potentiate the effect of AZT (3′-Azido-3′-deoxythymidine) in the anti-viral treatment of AIDS [ 27 ]. Its positive effects have been proved in the treatment of, e.g., glioma (human astrocytoma U251 cells) [ 46 ], breast cancer [ 47 ] and liver cancer [ 48 ]. In turn, the Turkey Tail ( Trametes versicolor (L.) Lloyd) contains characteristic proteoglucans.…”
Section: Nutritional Value and Bioactive Componentsmentioning
confidence: 99%